New Identities on Some Generalized Integral Transforms and their Applications - DERNEK, AYŞE NEŞE (My University, 2022)
© 2022, University of Nis. All rights reserved.In this paper the authors gave an iteration identity for the generalized Laplace transform L2n and the generalized Glasser transform G2n. Using this identity a Parseval-Goldstein type theorem for the L2n-transform and the G2n-transform is given. By making use of these results a number of new Parseval-Goldstein type identities are obtained for these and many other well-known integral transforms.The identities proven in this paper are shown to give rise to useful corollaries for evaluating infinite integrals of special functions. Some examples are also given.
Keywords: Temel Bilimler (SCI); Matematik; Natural Sciences (SCI); MATHEMATICS; Genel Matematik; Fizik Bilimleri; General Mathematics; Physical Sciences; E2n,1-transforms; G2n-transforms; Hv,n-transforms; Kv,n-transforms; Laplace transforms; Parseval-Goldstein type theo-rems